Influência do desempenho motor no futebol: uma revisão de literatura - Silva, Flavio Araujo da (Brasil, 2024)
Soccer develops in a complex context for decision making, because it has a dynamic characteristic of its nature, so the actions that students need have to be recreated and reconstructed through self organization and interaction where it is a process that depends on the component. situational. In recent years, most studies have focused on perceptual-cognitive skills associated with decision making, so that the student has a performance in the game, it is necessary for him to have a correct judgment of the task in which he is introduced. To provide useful information for planning soccer training, several authors develop scientific content to clarify issues inherent to training in the sport. That said, the present study aimed to perform a systematic search for articles in databases in Latin America that had results that would contribute to the development of planned soccer training. The results indicate that greater direction was found for research that relate the physical and maturational aspects in the performance of the modality, in addition to identifying that the coach plays a fundamental role in the modality, where their decisions can have a direct effect on the result of the practice. We conclude that motivational, anthropometric, physical and maturation-related aspects must be considered during soccer training planning.